2020
DOI: 10.1021/acschembio.0c00378
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial para-Hydroxybenzoic Acid-Derivatives (pHBADs) and Related Structures Induce Macrophage Innate Memory

Abstract: Macrophages are key immune cells for combatting Mycobacterium tuberculosis. However, M. tuberculosis possesses means to evade macrophage bactericidal responses by, for instance, secretion of the immunomodulatory para-hydroxybenzoic acid derivatives (pHBADs). While these molecules have been implicated in inhibiting macrophage responses in an acute context, little is known about their ability to reprogram macrophages via induction of long-term innate memory. Since innate memory has been highlighted as a promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous work has shown that exogenous radiolabeled p HB is taken up by mycobacterial cells and metabolically incorporated into cell–surface PGL . While p HB is also used in the biosynthesis of other p -hydroxybenzoic acid derivatives ( p HBADs), these metabolites are not associated with the cell envelopethey are either cytosolic or secretedand therefore would not be expected to confound the visualization of membrane-associated PGL. We synthesized both 2- and 3-azido p HB as described in the Supporting Information.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous work has shown that exogenous radiolabeled p HB is taken up by mycobacterial cells and metabolically incorporated into cell–surface PGL . While p HB is also used in the biosynthesis of other p -hydroxybenzoic acid derivatives ( p HBADs), these metabolites are not associated with the cell envelopethey are either cytosolic or secretedand therefore would not be expected to confound the visualization of membrane-associated PGL. We synthesized both 2- and 3-azido p HB as described in the Supporting Information.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous work has shown that exogenous radiolabeled pHB is taken up by mycobacterial cells and metabolically incorporated into cell-surface PGL. 8 While pHB is Phenolphthiocerol, phenolphthiodiolone, or phenolphthiotriol also used in the biosynthesis of other p-hydroxybenzoic acid derivatives (pHBADs), [36][37][38][39] these metabolites are not associated with the cell envelope -they are either cytosolic or secreted -and therefore would not be expected to confound the visualization of membrane-associated PGL. We synthesized both 2-and 3-azido pHB as described in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, there is a risk that certain immune challenges could lead to innate immune re-programming that hinders protective immune responses. For instance, recent reports have demonstrated how virulent M. tuberculosis ( Khan et al, 2020 ) and mycobacterial phenolic glycans ( Lundahl et al, 2020 ) can program macrophages to attenuate bactericidal responses to subsequent mycobacterial challenge. In the current study, macrophage activation caused by former or concurrent parasitic infections is considered regarding the possibility of innate immune re-programming that hinders protective immune responses against this disease.…”
Section: Introductionmentioning
confidence: 99%